Incidence and Risk Factors for Posterior Cruciate Ligament Avulsion during Cruciate Retaining Total Knee Arthroplasty - Kim, Eric; Talmo, Carl T.; Anderson, Marie C.; Bono, Olivia J.; Bono, James V. (The Journal of Knee Surgery, 2019)
During cruciate retaining (CR) total knee arthroplasty (TKA), the posterior cruciate ligament (PCL) may avulse at its insertion. The incidence of PCL avulsion fracture has not been previously studied. The aim of this study is to report on the incidence and clinical significance of intraoperative PCL avulsion during primary CR TKA and to identify potential risk factors. Our institutional joint registry was retrospectively reviewed for PCL avulsion occurring during CR TKA implanted between April 2008 and April 2016. Patient demographics, preoperative range of motion (ROM), complications, and revision rate were examined. A control group of 132 patients was used for comparison to identify potential risk factors. Forty-four of 2,457 patients (1.7%) suffered a PCL avulsion fracture during primary CR TKA. No intraoperative repair was performed and no postoperative weight bearing or ROM restrictions were implemented. There was no significant difference in BMI (p = 0.258), mean preoperative ROM (p = 0.763), or femoral and tibial component sizes (p = 0.3069, p = 0.1306) between groups. Logistic regression found female gender (p = 0.0254) to be the only statistically significant risk factor for PCL avulsion. The incidence of intraoperative PCL avulsion fracture during CR TKA is low (1.7%) and does not appear to affect postoperative ROM, subjective stability, or incidence of revision. Female gender was identified as the only patient factor that increased the risk of PCL avulsion fracture.
Keywords: posterior cruciate ligament avulsion; cruciate retaining; total knee arthroplasty